Klasifikasi Hadis Ditinjau Dari Segi Kuantitas Dan Kualitas Sanad - Utrianto Utrianto (MGMP PAI SMP BINTAN, 2022)
Hadith is the main source of Islamic teachings after the Qur'an. Hadith or also called Sunnah is everything that originates or is based on the Prophet SAW, whether in the form of words, deeds, or his taqrir. Discussions related to Hadith Science are always interesting studies, therefore this article focuses on the classification of hadith in terms of the quantity and quality of the sanad. So that the quantity and quality of a hadith can be known from the point of view of the distribution of its sanad. This study uses literature review which is expected to contribute to understanding regarding the classification of hadith. From the results of data analysis, the division of hadith is necessary in an effort to classify hadith, in terms of quantity the distribution of hadith aims to find out the number of narrators at each level so that classifications of muwatitir hadith, ahad hadith, famous hadith, hadith 'aziz and gharib hadith emerge. Meanwhile, in terms of quality, it aims to determine the authenticity of the hadith in terms of its shahih, hasan and daif.